Managing Eclampsia in a Medical College - RC, LK; Shrestha, S; Das, CR (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The aim was to analyze patient’s age, gestational age, mode of delivery, types of complication, fetomaternal outcome and prognosis in eclampsia. Methods: This was a retrospective one year study done at Nepalgunj medical college from June 2009 to May 2010. Results: Out of 21 (1.11%) eclampsia, nine (42.85%) were <20 years, nine (42.85%) were at term and 15 (71.43%) were primi para. Systolic blood pressure recorded >160 mm Hg in eight (38.10%) and diastolic blood pressure recorded 91-100 mm Hg were nine (42.8%). Antepartum and intrapartum eclampsia were 18 (85.72%) and two (9.52%) respectively. Nine (42.86%) had lower segment cesarean section. Ten (47.62%) babies were alive. All the patients were treated with magnesium sulphate and survived. Conclusions: Most of the patients in this study were primi para at term pregnancy. Patients were treated with magnesium sulphate that prevented maternal mortality. DOI: http://dx.doi.org/10.3126/njog.v9i1.11195 NJOG 2014 Jan-Jun; 2(1):74-77